IMPLEMENTATION OF PLS-PM IN KNOWING THE FACTORS THAT INFLUENCE THE INCIDENCE OF TYPHOID FEVER IN PATIENTS IN ANUTAPURA PALU HOSPITAL - Damayanti, Virga; Fadjryani, Fadjryani; Setiawan, Iman (PATTIMURA UNIVERSITY, 2025)
Typhoid fever is a multifactorial disease that has factors that can have an impact, including individual characteristics, maternal knowledge, hygiene, and nutritional status. Data on the incidence of typhoid fever involves many variables that cannot be examined directly (latent variables). This study used secondary data obtained from the medical records of typhoid fever patients at Anutapura Palu Hospital in 2023. One of the statistical methods that can be used to explain the relationship between indicators and latent variables is Partial Least Squares-Path Modeling (PLS-PM). Therefore, this study aims to model the influence of individual characteristics, maternal knowledge, hygiene, and nutritional status on the incidence of typhoid fever in patients at Anutapura Palu Hospital using PLS-PM analysis. The results of the PLS-PM analysis show that individual characteristics and nutritional status have a direct effect on the clinical images, while maternal knowledge and hygiene indirectly affect the clinical images through nutritional status, with a coefficient of determination of 0.828. So, it can be said that nutritional status is able to mediate between individual characteristics, maternal knowledge, and hygiene with the clinical images of typhoid fever.